The Social Ecology of Residential Patterns and Membership in Immigrant Churches - Ebaugh, Helen Rose; O'Brien, Jennifer; Chafetz, Janet Saltzman (Journal for the scientific study of religion, 2000)
In this paper, we utilize GIS (Geographic Information System) mapping data to locate eleven immigrant congregations and the residential addresses of their members in Houston, Texas. Combining this information with ethnographic data allows us to understand how ecological variables impact organizational characteristics of religious institutions. Specifically, we combine GIS and ethnographic data on immigrant congregations in Houston, Texas, to analyze characteristics that make them more parish or niche-like in structure. We demonstrate that the combination of GIS techniques and standard field methods yields the greatest potential to provide a comprehensive understanding of what congregations mean to their members.